2021
DOI: 10.1111/joor.13228
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcomes with the single‐puncture and double‐puncture techniques of arthrocentesis of the temporomandibular joint: An updated systematic review and meta‐analysis

Abstract: Objective To compare intra‐operative and postoperative outcomes between the single‐puncture and the standard double‐puncture techniques of arthrocentesis. Methods PubMed, Embase, ScienceDirect and CENTRAL databases were searched from inception up to 31st August 2020. Randomised controlled trials (RCTs), prospective and retrospective studies conducted on patients with temporomandibular joint disorders comparing any type of single‐puncture arthrocentesis with standard double‐puncture arthrocentesis and reporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…Among the minimally invasive puncture techniques within TMJ, lavage of the joint cavity, supplementation of hyaluronic acid (HA) and administration of corticosteroids (CS) are commonly known and used [5][6][7]. TMJ arthrocentesis is effective in the domains of pain relief and increases the extent of mandibular abduction [8][9][10][11]. The administration of HA complements the main component of the synovial fluid and is also referred to as viscosupplementation [6].…”
Section: Introductionmentioning
confidence: 99%
“…Among the minimally invasive puncture techniques within TMJ, lavage of the joint cavity, supplementation of hyaluronic acid (HA) and administration of corticosteroids (CS) are commonly known and used [5][6][7]. TMJ arthrocentesis is effective in the domains of pain relief and increases the extent of mandibular abduction [8][9][10][11]. The administration of HA complements the main component of the synovial fluid and is also referred to as viscosupplementation [6].…”
Section: Introductionmentioning
confidence: 99%
“…We were unable to acquire the full texts of eight citations for review, and our attempts to contact study authors were unsuccessful (appendix 3). Twenty four trials reported only surrogate outcomes (such as passive jaw opening, pain on palpation), 23 trials compared similar interventions that our clinical experts advised should be collapsed (for example, different types of removable oral splints, two-needle arthrocentesis v single-needle arthrocentesis; none of which showed different treatment effects651) and thus became observational data, and 10 trials compared interventions that are not typically available in current practice (supplement table 1). Thus, our meta-analyses included 153 studies from 172 references, which enrolled 8713 patients with chronic TMD pain.…”
Section: Resultsmentioning
confidence: 99%
“…Arthrocentesis is the simplest form of surgical treatment for the management of TMJ internal derangements, TMJ osteoarthritis, degenerative temporomandibular disorders, and conditions refractory to conservative treatment. [5][6][7][8] Several studies have shown that both arthrocentesis techniques have beneficial effects on pain intensity articular sounds, and mandibular range of motion; [19][20][21][22][23][24] however, there is no consensus on the superiority of one over the other. A systematic review has reported that SPA techniques are as clinically effectual as DPA in terms of pain intensity; maximum mouth opening; and other outcome variables, such as duration of surgery and patient satisfaction; however, the researchers have underscored the necessity of well-designed randomized controlled trials that will compare the two techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Several distinguished studies from the literature have compared different arthrocentesis techniques according to various parameters as; maximal mouth opening, pain, puncture-related complications, and irrigation efficiency. [19][20][21][22][23][24][25] To obtain more precise results for determining the technique in clinical environment; clinician satisfaction should also be compared. The aim of this study was to evaluate the clinician satisfaction of single-puncture arthrocentesis (SPA) and double-puncture arthrocentesis (DPA) in cadavers.…”
mentioning
confidence: 99%